Hubungan Gaya Belajar dengan Penguasaan Konsep dan Keterampilan Pemecahan Masalah Pendahuluan Fisika Inti Mahasiswa Calon Guru - Lukman Hakim; Patricia Hotma Minar Lubis; Lefudin Lefudin; Rita Sulistyowati (Postgraduate, University of Mataram, 2022)
Many factors that influence the students’ learning achievement include the learning styles. If the teacher presents learning according to the student's learning style, it will have an impact on maximum student learning outcomes. Student learning outcomes could be in the form of problem solving skills and mastery of students' preliminary concepts of nuclear physics. Problem solving ability is an important ability that must be possessed by students in facing the era of the industrial revolution 4.0. Therefore, the purpose of this study was to obtain an overview of learning styles, problem solving abilities and mastery of student teacher concepts for this physics introduction. The method used in this research was a case study with a sample of 35 physics teacher candidates at a private university in the city of Palembang. The learning applied is traditional learning with interactive multimedia-assisted presentation method. The results showed that the predominant primary learning style of nuclear physics students was auditory, while the average problem-solving ability and mastery of preliminary nuclear physics concepts were 89 and 93, respectively, with very high categories. The results of this study become input in the development of the nuclear physics preliminary lecture.